Priority-setting in food and agricultural policy research: a case study and lessons from Malawi. - Babu, Suresh Chandra; Khaila, Stanley (1996)
This paper develops a conceptual framework for setting priorities in public policy research at a country level. Using the conceptual framework as a guide, a case study of priority-setting in food and agricultural policy research in Malawi is presented. Lessons are derived from the Malawi approach for similar attempts elsewhere. Priority-setting in policy research provides an opportunity to better organize the research programs and to ensure the user participation in policy research for increased use of research information in policy decisionmaking. It is argued that the process of priority-setting in policy research should be seen as an integral part of the process of policy formulation and implementation.